1973
DOI: 10.1203/00006450-197303000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Amino Acid Loss and Its Significance in Infantile Diarrhea

Abstract: ExtractSignificant amino acid loss through the stool, analogous to impeded reabsorption of water, fat, and electrolytes, was suspected in infantile diarrhea. The stools of six patients, who had acute diarrhea and received no protein by mouth, were collected and analyzed for amino acids, nitrogen, and protein. Similar determinations were made on five normal controls. In addition, stool collections were made from one patient during a severe protracted diarrhea which necessitated parenteral alimentation, during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Another possible source is the amino-acid pool. Although this is labelled with significant amounts of 15N the level of enrichment falls rapidly.5 Ghadimi et al 13 found markedly increased levels of amino-acid in the stool in diarrhoeal disease as well as increased loss of protein and total nitrogen. Whatever the source of the endogenous faecal nitrogen, the losses in stool were so great that it is unlikely that the infants had sufficient nitrogen available for tissue repair let alone normal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible source is the amino-acid pool. Although this is labelled with significant amounts of 15N the level of enrichment falls rapidly.5 Ghadimi et al 13 found markedly increased levels of amino-acid in the stool in diarrhoeal disease as well as increased loss of protein and total nitrogen. Whatever the source of the endogenous faecal nitrogen, the losses in stool were so great that it is unlikely that the infants had sufficient nitrogen available for tissue repair let alone normal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Other than fasting, two factors can disturb plasma amino acids levels among these children: diarrhea by itself and hydroelectrolytic perfusion. If, during diarrhea, there is an increase of amino acid spoilage by feces, it becomes substantial in severe and refractory diarrhea (9). Group 111 patients never suffered from severe diarrhea.…”
Section: Groups Of Patientsmentioning
confidence: 99%
“…Wannemacher has hypothesized that low levels of serum branchedchain amino acids during some infections are due to increased catabolism of these amino acids by muscle tissue as sources of energy (26). Shigella enterotoxin (1) and diarrhea (7) have been implicated in the inhibition of transport and malabsorption of amino acids by intestines, as well as in the creation of deficiencies of minerals and vitaxmins. Therefore, a host may become deficient in essential amino acids due to diet or infection.…”
mentioning
confidence: 99%